ANALISIS PENERAPAN PRINSIP “5C” TERHADAP AKURASI ANALISA KREDIT PADA PT. FIRST INDO AMERICAN LEASING - Marwansyah, Sofyan (Universitas Bina Sarana Informatika, 2014)
The company is one of the economic actors. Leasing or lease is a financial company whose activities provide financing facilities. Definition of the lease based on the Ministry of Finance No.1969 / KMK.01 / 1999 Article 1, the rent-to-business (leasing) is a financing activity in the form of supply of capital goods either lease with the option-business (finance lease) or rental -guna-effort without the option (operating lease) for use by the lessee for a certain period based on periodic payments. nonperforming loans originated from the accuracy of credit analysts conduct analysis on prospective customers, the tighter the analysts to analyze the problem loans will not occur or be minor. In this study the authors will discuss the principles of Applied 5c to the accuracy of the analysis of PT First Indo American Leasing by distributing questionnaires to 30 credit analysts, the results of that discussion dipeoleh There is a strong and direct relationship between the application of the principle of 5c on the accuracy of analysis, where the better implementation 5C principle it will better the accuracy of the analysis of the provision of credit, the amount of analysis accuracy is affected by the application of the principle of 5C in your analysis process credit of 72.10% remaining 27.9% is influenced by other factors and the regression equation Y = 0.480 + 0.919 x is the regression equation significant. Keywords : accuracy analysis, principle 5 C,